Study of noise pollution in the area surrounding Delta Avenue using the app of Geographic Information Systems - Carrasco Vargas , Viviana Carolina; Sánchez Vélez , Gladys Milena; Colorado Pástor, Bryan Alfonso (Artes: Architecture, Technology and Sustainability, 2022)
The present research work evaluated the level of noise pollution in the area surrounding the University of Guayaquil, prioritizing the activity in the Avenidad Delta, located. The study was situated in the morning, evening and night hour analysis, where it is observed that among the possible causes is the agglomeration of vehicles responsible for the emission of noise due to the excessive use of horns. The methodology focuses on the qualitative and quantitative analysis of the problem using participant observation and noise capture through the sound level meter (db) application, exercise clusters of influence in certain areas. According to the results, most of the points in the study area exceed the maximum permissible noise limits. In addition to monitoring, a noise map showing the sound pressure intensities at each point was made using ArcGIS software. It is concluded that noise emissions are in a range from very annoying to very strong, for which strategies should be used that prevent the direct passage of noise to maintain the state of noise to intrusive and unnoticed, which helps concentration and development. of study activities.